Endoscopic Removal of a Supernumerary Premolar in the Mandible during a Dental Implant Placement - Víctor Beltrán; Mario Cantín; Eduardo Borie; Ramón Fuentes; Wilfried Engelke (Case Reports in Dentistry)
The surgical removal of supernumerary teeth is necessary in some cases, especially before the commencement of any orthodontic or implant treatment procedure. In the mandibular supernumerary premolar, a more conservative approach is required because of the presence of complications associated with conventional surgery due to the close proximity of the said premolar to the alveolar inferior and mental nerves, and the need for bone conservation for implant placement. The endoscopic surgical approach has been used for the removal of the maxillary supernumerary tooth, impacted third molar, and implants. In this case report, we present an endoscopically assisted surgical technique for the removal of an unerupted supernumerary premolar in the mandible associated with a dental implant placement procedure.